A Signification Analysis of Jiwa Toast Collaboration Poster: Culinary Commodification - Indah Septiar; Ahmad Jum’a Khatib Nur Ali (Riwayat: Educational Journal of History and Humanities, 2025)
One of the culinary arts related to culture and creativity is bread. Bread making in Indonesia generally refers to the open-top bread from England which began to be popular in the 1800s. This type of bread is also commonly called white bread in Indonesia. This type of open-top bread is also known as sandwich bread in America after World War II. This type of bread has also become a cultural product that has become the cultural identity of England and America. This study focuses on how Jiwa Toast as an Indonesian brand builds a bread menu that is in accordance with Indonesian culture and commodifies culture through posters. This study uses a constructivist paradigm approach, with qualitative methods and theories of signification and habitus as analytical tools. The results of the study show that the collaborative advertising poster for the "Beef Rendang" and "Tuna Lando Mundo" menus combines local and global elements. Denotatively, the poster features close-up images of both dishes to showcase the deliciousness of the products, while the text and visual symbols emphasize the unique collaboration between local Indonesian food and global inspiration. Connotatively, rendang symbolizes traditional values, authentic cooking processes, and Indonesian cultural heritage. In contrast, "Tuna Lando Mundo" implies a modern and global feel, creating a refreshing blend of flavors. This commodification shows how original cultural meanings can be replaced by commercial values, following the trend of consumerism.